2016
DOI: 10.1063/1.4948732
|View full text |Cite
|
Sign up to set email alerts
|

Transport and trapping of dust particles in a potential well created by inductively coupled diffused plasmas

Abstract: A versatile linear dusty (complex) plasma device is designed to study the transport and dynamical behavior of dust particles in a large volume. Diffused inductively coupled plasma is generated in the background of argon gas. A novel technique is used to introduce the dust particles in the main plasma by striking a secondary direct current (DC) glow discharge. These dust particles are found to get trapped in an electrostatic potential well which is formed due to the combination of the ambipolar electric field c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…They get negatively charged in the plasma and [34,35] To record the dynamics of the confined dust particles, a red laser to illuminate the dust and a CCD camera to record the scattering light from the grains are used. At ground-based experiments, a large volume dusty plasma is possible either in specific discharge configuration [17,37] or discharges with nano to sub-micron sized particles. These stored images are further analysed using MATLAB based code and ImageJ software.…”
Section: Dust Acoustic Waves and Its Characteristics In Absence Of Mamentioning
confidence: 99%
“…They get negatively charged in the plasma and [34,35] To record the dynamics of the confined dust particles, a red laser to illuminate the dust and a CCD camera to record the scattering light from the grains are used. At ground-based experiments, a large volume dusty plasma is possible either in specific discharge configuration [17,37] or discharges with nano to sub-micron sized particles. These stored images are further analysed using MATLAB based code and ImageJ software.…”
Section: Dust Acoustic Waves and Its Characteristics In Absence Of Mamentioning
confidence: 99%
“…The experiments are performed in a cylindrical linear device, which is described elsewhere 41 in details. The schematic of the experimental assembly with an operating configuration is depicted in Fig.…”
Section: Experimental Setup and Diagnosticsmentioning
confidence: 99%
“…For injecting the kaolin dust particles (ρ d ∼ 2.6 gm/cm 3 and r d ∼ 0.5 to 5 µm) into the confining potential well, a secondary DC plasma source is used 41 . As these particles come into the plasma volume, they start to flow in the ambipolar electric field of diffused plasma and found to confine in the potential well created by the diffused plasma 41 .…”
Section: Experimental Setup and Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, the co-rotating vortices are observed in an extended unmagnetized dusty plasma 20 . The charge gradient of dust grains along with the ion drag force, which is due to the plasma inhomogeneity along the dust cloud axis, is considered the source of vortex flow 20,44 . These observed exciting results on the corotating vortices have been created an interest to study the large aspect ratio dusty plasma in inhomogeneous plasma background.…”
Section: Introductionmentioning
confidence: 99%